2018
DOI: 10.1038/s41467-018-07141-w
|View full text |Cite
|
Sign up to set email alerts
|

Customizing supercontinuum generation via on-chip adaptive temporal pulse-splitting

Abstract: Modern optical systems increasingly rely on complex physical processes that require accessible control to meet target performance characteristics. In particular, advanced light sources, sought for, for example, imaging and metrology, are based on nonlinear optical dynamics whose output properties must often finely match application requirements. However, in these systems, the availability of control parameters (e.g., the optical field shape, as well as propagation medium properties) and the means to adjust the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 49 publications
0
42
0
2
Order By: Relevance
“…Genetic algorithms can also be used for these purposes, and their application to solve highly nonlinear optimisation problems such as fibre supercontinuum generation has also been very successful [44][45][46][47]. Using custom pulse train preparation via an integrated pulse-splitter, a genetic algorithm was used to optimize supercontinuum dynamics to maximize spectral intensity in specific wavelength bands [47] (Fig. 4B).…”
Section: Control Of Coherent Dynamicsmentioning
confidence: 99%
“…Genetic algorithms can also be used for these purposes, and their application to solve highly nonlinear optimisation problems such as fibre supercontinuum generation has also been very successful [44][45][46][47]. Using custom pulse train preparation via an integrated pulse-splitter, a genetic algorithm was used to optimize supercontinuum dynamics to maximize spectral intensity in specific wavelength bands [47] (Fig. 4B).…”
Section: Control Of Coherent Dynamicsmentioning
confidence: 99%
“…Optical fibers have been the primary medium for supercontinuum generation for their strong confinement of pump laser light, as well as for the feasibility of chromatic dispersion engineering, which significantly simplifies matching of the nonlinear medium's optical properties to intended pump lasers, compared to non-fiber systems (Alfano and Shapiro 1970a, b;Dudley et al 2006). Coherent and spectral properties of fiber-based supercontinuum can be widely modified to fulfill various application requirements (Klimczak et al 2017;Wetzel et al 2018;Genier et al 2019). In 2000, Ranka et al (2000) demonstrated for the first time supercontinuum generation in photonic crystal fibers (PCFs).…”
Section: Introductionmentioning
confidence: 99%
“…В статье [4] рассмотрены различные способы генерирования импульсов Найквиста с использованием оптоэлектронных и оптических компонентов, а также дана обширная библиография. В работе [5] рассматривается группа методов управления формой НЧС оптического сигнала с использованием импульсов лазера длительностью порядка 200 фс и оптического волокна с нелинейной передаточной характеристикой. Определенным ограничением предлагаемых в работах [2][3][4][5] методов является их ограниченная универсальность: они дают хорошие результаты для определенных форм НЧС.…”
Section: Introductionunclassified
“…В работе [5] рассматривается группа методов управления формой НЧС оптического сигнала с использованием импульсов лазера длительностью порядка 200 фс и оптического волокна с нелинейной передаточной характеристикой. Определенным ограничением предлагаемых в работах [2][3][4][5] методов является их ограниченная универсальность: они дают хорошие результаты для определенных форм НЧС. Принципиальная возможность аппроксимации произвольной НЧС короткими импульсами лазера гауссовой формы дана в работах [6,7], а в статье [8] дана более общая теория.…”
Section: Introductionunclassified